A model-based analysis of CO2 utilization in methanol synthesis plant. Issue 10 (June 2015) - Milani, Dia; Khalilpour, Rajab; Zahedi, Gholamreza; Abbas, Ali
Abstract: Utilizing the greenhouse gas CO2 as a feedstock in chemical processing could offer alternative solutions to long-term storage. Large-scale production of light hydrocarbons such as methanol (MeOH) is one of the predominant and sensible schemes for such utilization. This proposal will not only recycle the CO2 gas within methanol synthesis process, but will also reduce the uptake of raw materials such as natural gas (NG) and reduce the greenhouse-gas (GHG) emissions of a comparable stand-alone NG-based methanol synthesis plant. In this paper, a comprehensive model for CO2 integration in NG-based methanol synthesis plant has been developed. The reformer product (syngas) is mixed with the high-purity CO2 stream that comes out of power-plant carbon capture (PCC) process. It is found that this integration may reduce methane uptake by 25.6% and decrease the combined CO2 emissions for both power-plant and MeOH-plant by 21.9%. The energy intensity for this integration is 33.45 GJ th /tonne MeOH and 0.64 GJ el /tonne MeOH . The energy efficiency of this integration is 59% and the product to feed ratio is 2.27 tonne MeOH /tonne CH 4 higher than 1.69 tonne MeOH /tonne CH 4 calculated for a comparable standalone NG-based methanol synthesis plant with 68% efficiency.